New alkenyl derivative from Piper malacophyllum and analogues: Antiparasitic activity against Trypanosoma cruzi and Leishmania infantum. (3rd May 2017) - Varela, Marina T.; Lima, Marta L.; Galuppo, Mariana K.; Tempone, Andre G.; de Oliveira, Alberto; Lago, João Henrique G.; Fernandes, João Paulo S.
Abstract : Alkylphenols isolated from Piper malacophyllum (Piperaceae), gibbilimbols A and B, showed interesting activity against the parasites Trypanosoma cruzi and Leishmania infantum . In continuation to our previous work, a new natural product from the essential oil of the leaves of P. malacophyllum was isolated, the 5‐[(3 E )‐oct‐3‐en‐1‐il]‐1, 3‐benzodioxole, and also a new set of five compounds was prepared. The antiparasitic activity of the natural product was evaluated in vitro against these parasites, indicating potential against the promastigote/trypomastigote/amastigote forms (IC50 32–83 μm ) of the parasites and low toxicity (CC50 > 200 μm ) to mammalian cells. The results obtained to the synthetic compounds indicated that the new derivatives maintained the promising antiparasitic activity, but the cytotoxicity was considerably lowered. The amine derivative LINS03011 displayed the most potent IC50 values (13.3 and 16.7 μm ) against amastigotes of T. cruzi and L. infantum, respectively, indicating comparable activity to the phenolic prototype LINS03003, with threefold decreased (CC50 73.5 μm ) cytotoxicity, leading the selectivity index (SI) towards the parasites up to 24.5. In counterpart, LINS03011 has not shown membrane disruptor activity in SYTOX Green model. In summary, this new set showed the hydroxyl is not essential for the antiparasitic activity, and its substitution could decrease the toxicity to mammalian cells. Abstract : Alkenylbenzene molecules isolated from Piper malacophyllum have shown promising antiparasitic activity and low cytotoxicity. Several synthetic analogues were prepared to optimize the activity against Trypanosoma cruzi and Leishmania infantum . The amine analogues were the most promising.